IMPACT OF ADAPTIVE PHYSICAL EDUCATION ON HEALTH OF STUDENTS FROM VARIOUS NOSOLOGICAL GROUPS - Shumikhina, I.I.; Mitrichenko, R.Kh. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the impact of adaptive physical education on the health of students from various nosological groups. Methods and structure of the study. In the postoperative period, the students with disabilities, chronic diseases, and injuries were transferred to the adaptive physical education groups for health reasons. They attended adaptive physical education lessons twice a week, just as the main and preparatory groups. The lessons were disease-driven. The groups were formed of 8-10 students with due regard to their nosology, including 2-3 students with disabilities – with the same degree of the motor defect; students with different defects attended one-on-one training sessions. The physical loads for corrective purposes – to expand the motor sphere of the disabled students – were designed based on the knowledge of the specifics of functioning of the cardio-respiratory, nervous and locomotor systems. Results and conclusions. Adaptive physical education classes designed for physically disabled students from various nosological groups were proved to facilitate the improvement of their adaptive capabilities and physical working capacity.